Pengaruh Minuman Cokelat terhadap Kadar VO2Max pada Atlet Futsal Politeknik Negeri Jember - Arisanty Nur Setia Restuti; Adhiningsih Yulianti; Wahyu Laely (Jurnal Kesehatan Amanah, 2025)
Nutrition influence to fulfill the energy when the athletes conducting exercise have to consider for the successful in conducting the activity. Cacao is a fruit that contain (4,10 kkal/gram) of carbohydrate, (9 kkal/gram) of fat, (4,1 kkal/gram) of protein, and antioxidants. Composition of cacao nutrition was beneficial to provide the energy in our body. This study was conductued to know the impact of giving a chocolate on VO2Max for athletes at Politeknik Negeri Jember. The method that have conducted was pre-experiment with one group pretest posttest program, because this study conducted pretest that try the alterations that have been conducted, then will be conducted again the experiment after posttest. The technique in get the subject of this study was use total sampling technique, where he amount of the subject that will be experimented is same with the population of the study that are 20 athletes. This study conducted at Politeknik Negeri Jember. The result of this study form independent test was known the value of significance is 0,012 (p<0,05) means that chocolate could increase VO2Max of athlete. The conclusion of this study was that there is an effect of giving chocolate to increase in maximal oxygen volume (VO2Max) for athletes.